Neoepitope BTLAP267L-specific TCR-T cell immunotherapy unlocks precision treatment for hepatocellular carcinoma - Fang Liu; Hua Chen; Suxin Wu; Chenlu Zhu; Mingji Zhang; Wei Rui; Dong Zhou; Yang Wang; Xin Lin; Xueqiang Zhao; Yunbin Ye (Cancer Biology & Medicine)
Objective: The high heterogeneity of hepatocellular carcinoma (HCC) renders traditional therapies unable to effectively activate the patient’s immune system to combat tumors. Patients with advanced HCC and T cell functional deficiencies may benefit more from cellular immunotherapy, especially tumor neoepitope-targeted T cell receptor (TCR)-T cells. Neoepitopes with strong immunogenicity provide precise targets for HCC, further enhancing the efficacy of cellular immunotherapy. Methods: A scalable workflow for identifying neoepitopes from 7 HLA-A*02:01-restricted patients with HCC was established based on whole exome sequencing and bioinformatics analyses, followed by identification of neoepitope-specific TCRs through tetramer-based screening and single-cell TCR cloning technology, which were further validated in the JC4 cell model. The cytotoxicity of CD8+ TCR-T cells was evaluated in neoepitope-positive tumor cell lines or NCG mice. Results: Ten specific neoepitopes were identified, among which neoepitope B and T lymphocyte attenuatorP267L [BTLAP267L (SLNHSVIGL)] exhibited advantageous properties as a potential tumor target. Three TCRs (85-3, 126-5, and 52-3) were confirmed to specifically recognize the neoepitope BTLAP267L, while no cross-recognition of irrelevant or wild-type epitopes was observed. Activated BTLAP267L-specific CD8+ TCR-T cells released extensive perforin, granzyme B, IFN-γ, and TNF-α in vitro , thereby inducing strong cytotoxic effects against BTLAP267L-positive T2 or HCC cell lines. BTLAP267L-specific CD8+ TCR-T cells mediated robust tumor regression due to long-lasting survival and released perforin without causing significant cytotoxic effects on normal organs in murine experiments. Conclusions: This preclinical study demonstrated the beneficial effects of neoepitope BTLAP267L-specific TCR-T cell immunotherapy, unlocking a novel strategy for personalized precision therapy in HCC.